Fenomena Korupsi Pejabat Publik di Jawa Barat - Nur Atnan (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2014)
The purposes of this research to know and described corruption pattern conducted by government officials, the causes of corruption involving government officials, and effective solution in combating corruption in West Java that should be taken by the law enforcement institutions. This research based on qualitative method by literature research and in depth interview. The research founds that corruption committed in West Java mostly in form of State Budgeting Loss meanwhile; the causes of corruption in West Java were high political cost and taking the loopholes of such regulation. So, It can be solved by the law enforcement institutions must perform better in the eradication of corruption by repairing three sectors such as regulation, organizational structure and legal culture of the officers.